Discrete Power Control in Heterogenous Networks - Wang, Yuanyuan; Hardjawana, Wibowo; Vucetic, Branka (UI Scholars Hub, 2016)
In heterogeneous networks (HetNets) where femtocell base stations (FBSs) are deployed within the radio coverage of macrocell base stations (MBSs) to increase network capacity, co-channel interference limits overall system performance with universal frequency reuse. This paper investigates new distributed downlink discrete power control scheme for FBSs in HetNets with FBSs cooperation. The objective of the proposed power control scheme is to maximize the number of simultaneous FBSs transmissions in a single transmission wireless channel where each FBS is allowed to transmit only if the signal-to-interference-noise ratio (SINR) requirements for both FBSs and MBS users are satisfied. We apply a stochastic learning automata technique to FBSs where each FBS is treated as a learning automaton and maintains a probability vector to select its discrete transmit power. During the learning process, each FBS adjusts its probability vector based on the feedback from FGW that indicates the number of FBSs transmissions that can be supported under the SINR requirement constraints of FUEs and MUEs. Simulation results show the proposed algorithm can achieve more than twice the number of simultaneous FBS transmissions achieved by existing schemes in the literature.